Comparison of Attachment and Relaxation Training Effects on Anxiety in Third Trimester and Postpartum Depression among Primipara Women - Bahare Rafiee; Marzieh Akbarzade; Nasrin Asadi; Najaf Zare (Tehran University of Medical Sciences, 2013)
Background & Aim: Reducing maternal anxiety has a critical role in maternal and fetal mental and physical health. This study aimed to assess the effect of two anxiety reducing techniques including relaxation and maternal-fetal attachment training on anxiety in third trimester and postpartum depression among primipara women.   Methods & Materials: In this clinical trial, 126 pregnant women were randomly selected and divided into three groups including relaxation training, maternal-fetal attachment skills training, and control group. The participants completed a demographic questionnaire, the Spillberger and Beck questionnaires and written consents at baseline. The participants completed the questionnaires after the intervention too. The one way ANOVA and paired t-test were used to analyze the data.    Results: At baseline, the mean total anxiety, state and trait anxiety and depression scores were not significantly different between the groups. The ANOVA showed differences in the mean score of anxiety after the intervention (P=0.03) in the intervention groups. There were statistically significant differences between the attachment and control groups (P=0.01) and the relaxation and control groups (P<0.001) in terms of the mean score of state anxiety. The ANOVA showed a reduction in the mean score of state anxiety after intervention in the attachment (P=0.02) and relaxation groups (P=0.01). There was significant difference after the intervention in the mean score of maternal depression (P=0.002) between the attachment and relaxation groups with the control group (P=0.01, P=0.01 respectively).    Conclusion: A ttachment and relaxation trainings can reduce maternal anxiety and post-partum depression. Pregnancy visit is an important opportunity to screen maternal anxiety and prevent post-partum depression using simple and non-expensive training programs.